2021
DOI: 10.54289/jdoe2100109
|View full text |Cite
|
Sign up to set email alerts
|

What do Patients Use for Treating Their Oral Ulcers? And How do these Treatments Affect Their Quality of Life?

Abstract: Objectives: Oral ulceration forms a major category of oral lesions. Due to its effect on the quality of life, the patients seek treatment using various substances. This study investigated the types of treatments used by a sample of patients having all types of oral ulcers and its positive and negative effects on the patients' lives. Methods: This cross-sectional study included patients having different types of oral ulcers. Participants provided information about their previous treatments, the source of recomm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
1
0
0
Order By: Relevance
“…In general, in the present study, the recovery time of aphthous ulcers, defined as the time interval, in days, between the start of treatment and complete healing, with no pain, no fever, no drooling and no eating or drinking difficulty was significantly shortened in the honey group, being 8.7 days, compared to 12.8 days in the children who did not receive honey (P=0.000). These positive effects of honey on aphthous ulcers were also observed in the studies of Samet et al ( 2007 (46,14,47,44,48,43) . On the other hand, in the treatment of minor recurrent aphthous stomatitis of 20 patients, Halim et al (2013) found in their study no significant difference between the honey and salicylate gel groups, with regard to pain score improvement (49) .…”
Section: Discussionsupporting
confidence: 77%
“…In general, in the present study, the recovery time of aphthous ulcers, defined as the time interval, in days, between the start of treatment and complete healing, with no pain, no fever, no drooling and no eating or drinking difficulty was significantly shortened in the honey group, being 8.7 days, compared to 12.8 days in the children who did not receive honey (P=0.000). These positive effects of honey on aphthous ulcers were also observed in the studies of Samet et al ( 2007 (46,14,47,44,48,43) . On the other hand, in the treatment of minor recurrent aphthous stomatitis of 20 patients, Halim et al (2013) found in their study no significant difference between the honey and salicylate gel groups, with regard to pain score improvement (49) .…”
Section: Discussionsupporting
confidence: 77%